K-Means Clustering Segmentation Model Using SPSS: A Case Study at Komuka Cafe Customers - Agus Sugiono; Tika Aldyah; Milastri Muzakkar; Jerry Heikal (Jurnal Manajemen Bisnis Eka Prasetya, 2024)
Post pandemic has led to a significant and rapid increase in the growth of the cafe business. Every year, many new cafes emerge with different and unique concepts, intensifying competition in the cafe industry and necessitating continuous innovation for cafe entrepreneurs. Previously, Komuka has always highly recommended Google Reviews to prospective customers. This has caused Komuka's market share to stagnate and not experience meaningful growth. This research aims to enhance the marketing strategy of Komuka Cafe by applying K-Means cluster analysis for customer segmentation. Through data collection from Komuka's Cafe customers and klaster analysis using SPSS, the study identifies three main customer klasters: Single Employee, Married Employee, and Single Student. The detailed marketing strategy focuses on the Single Employee group because this cluster has the lowest assessment of Komuka Cafe. In this research, the author uses the Marketing Mix model 6Ps as a framework analysis to make strategy suggestions that need to be maintained and developed including Product, Place, Promotion, People, Process, and Physical Evidence. This research provides the preferences and behavior of Single Employee groups, Komuka Cafe can improve its 6Ps marketing strategy to increase competitive advantage, customer satisfaction and loyalty, as well as increase the revenue.